PENGGUNAAN APLIKASI MACROMEDIA FLASH 8 SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Muslikhatun Aimah; Haning Hasbiyati; Laila Khusnah (Pendidikan Biologi,Universitas Islam Jember, 2017)
The development of information technology has influenced the use of various types of media as a tool in the learning process. Based on the observation of biology learning process,it is explained that many students who didn’t do the homework and follow the biology lesson while learning process run in the classroom which difficult to learn biology and the language within it difficult to understand were the reason of them, that way the average of student learning outcomes are still low below the standards of KKM values. So researchers used Macromedia flash application as an interactive media to improve the student learning outcomes. This research used Classroom Action Research with data obtained using quantitative data derived from the test of learning outcomes and qualitative data obtained from classroom teacher interviews, document archives and student questionnaires. This research used the purposive technique with the respondent in 22 students. Based on the results of the students' assessment on cycle 1 and cycle 2 decided the grade average increased from 75 to 84.2 %,meanwhile the completion of classical learning increased from 81% to 100% and the result of classical student percentage analysis has 68% with good enough criteria. Based on both of comparison can be concluded that macromedia flash can improve student learning outcomes.